Formulation and evaluation of metformin-loaded microspheres using modified double emulsion solvent evaporation technique - Saikat Santra; Debraj Dey; Twinkle Pal; Abu Shoeb; Pinki Biswas (Journal of Applied Pharmaceutical Research, 2026)
Background: Metformin hydrochloride is the first-line therapy for Type 2 diabetes mellitus; however, its short biological half-life, low oral bioavailability, and frequent dosing often compromise patient compliance and cause gastrointestinal side effects. Sustained-release delivery systems may overcome these limitations. This study aimed to develop and evaluate ethylcellulose-based sustained-release metformin-loaded microspheres using a modified W/O/W double-emulsion solvent evaporation technique. Methodology: Six formulations (MF-M1 to MF-M6) were prepared by varying ethylcellulose concentrations (1.0–3.5% w/v). Microspheres were evaluated for percentage yield, entrapment efficiency (EE%), particle size, swelling index, surface morphology (SEM), thermal behavior (DSC), drug–polymer compatibility (FTIR), in-vitro drug release, and release kinetics. Results and Discussion: Increasing ethylcellulose concentration significantly improved yield (65.4–88.2%) and EE% (58.2–85.6%) while increasing particle size (48.2–121.5 µm). MF-M5 (3% EC) demonstrated optimal performance with high yield (85.6%), EE% (82.1%), controlled initial burst (7.2%), and sustained release (91.6% over 24 h). MF-M6 exhibited the longest release but showed a larger particle size and processing challenges. Drug release followed first-order and Higuchi kinetics, with anomalous transport observed at higher polymer levels. Conclusion: The modified W/O/W technique successfully encapsulated hydrophilic metformin into sustained-release microspheres. MF-M5 is identified as the most balanced formulation, while MF-M6 may be suitable where maximum release retardation is required.